Association of helmet use with traumatic brain and cervical spine injuries following bicycle crashes. (3rd May 2020) - Page, Paul S.; Burkett, Daniel J.; Brooks, Nathaniel P.
Abstract: Background: The use of bicycle helmets in preventing traumatic brain injuries (TBI) is frequently cited but data remain inconclusive. Additionally, the effects of helmets on cervical spine injuries (CSI) are debated. Methods: We performed a retrospective review of all adult patients with bicycle crashes presenting to one level 1 trauma center in Wisconsin from 2010 to 2016. Patients were divided into two groups: helmeted and un-helmeted. Results: In total 287 patients were included; 149 un-helmeted (51.9%) and 138 helmeted (48.9%). Helmeted riders had radiographic evidence of traumatic brain injury in 20.3% of cases compared to 40.3% of un-helmeted ( p  < 0.001). On average, helmeted riders had a similar injury severity score of 7.80 (standard deviation (SD) = 7.18) compared with 8.25 (SD = 9.98) in the un-helmeted group ( p  = 0.68). CSI occurred in 16 (10.7%) un-helmeted patients compared with 15 (10.9%) helmeted patients ( p  = 0.707). Of the un-helmeted group, four patients (2.7%) were found to have a cervical spine fracture compared with 12 (8.7%) helmeted patients ( p  = 0.037). Conclusion: Helmet use demonstrated a statistically significant advantage in the prevention of traumatic brain injuries. No significant difference was found regarding the incidence of severity of cervical spine injuries. These results do not demonstrate any statistically significant benefit in the prevention of cervical spine injuries with helmet use. In contrast, helmet use was found to convey a significant protective advantage in the prevention of traumatic brain injuries compared to no helmets.